2015
DOI: 10.1097/id.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Polymers and Their Potential Application as Medical and Oral Implant Materials

Abstract: The HPPs (ie, PEEK) may carry some potential to be an alternative material for titanium as medical and dental implants. Yet, clinical and animal studies are limited in the field of implantology with such materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 45 publications
1
90
0
Order By: Relevance
“…The results are confirmed by the observation that white blood cell total did not significantly change during the study, as well as compared to pre-implantation and compared to non-grafted mice. Other studies have also shown that titanium alloy (Granchi et al, 2008;Williams, 2001;Xu et al, 2013) and polymer (Dahmen et al, 1997;Wiesli and Özcan, 2015) are non-immunogenic materials.…”
Section: Dna Damage Evaluation By Comet Assaymentioning
confidence: 99%
“…The results are confirmed by the observation that white blood cell total did not significantly change during the study, as well as compared to pre-implantation and compared to non-grafted mice. Other studies have also shown that titanium alloy (Granchi et al, 2008;Williams, 2001;Xu et al, 2013) and polymer (Dahmen et al, 1997;Wiesli and Özcan, 2015) are non-immunogenic materials.…”
Section: Dna Damage Evaluation By Comet Assaymentioning
confidence: 99%
“…Conventional removable partial denture (RPD) frameworks are often fabricated from cobalt chromium (Co‐Cr), which has many drawbacks, such as allergic reactions, esthetic issues with the metal display, oral galvanism, and biofilm plaque formation. An alternative treatment option for patients having allergic reactions to Co‐Cr alloys is a metal‐free RPD . A polymer‐based framework consists of a modified poly(etheretherketone) (PEEK) polymer, bio high‐performance polymer (BioHPP) framework combined with acrylic resin denture teeth, and a conventional acrylic resin denture base.…”
mentioning
confidence: 99%
“…PEEK imparts its stiffness from aromatic benzene rings and its ability to rotate in an axial direction thanks to ether oxygen bonds. This material can be sterilized and irradiated due to its stability at temperatures above 300°C . PEEK and PEEK modified products are the most widely used high‐impact polymers in medical appliances and have been used in head, spine implant, and orthopedic surgeries with notable success .…”
Section: Definitive Abutments That Can Be Used With Titanium Fixturesmentioning
confidence: 99%
“…This material can be sterilized and irradiated due to its stability at temperatures above 300°C . PEEK and PEEK modified products are the most widely used high‐impact polymers in medical appliances and have been used in head, spine implant, and orthopedic surgeries with notable success . With stiffness double that of lithium disilicate and similar to cortical bone, this material can alleviate excessive stress being directed on implants and provide lesser stress shielding, a characteristic also noted in trauma and orthopedic reconstructions.…”
Section: Definitive Abutments That Can Be Used With Titanium Fixturesmentioning
confidence: 99%
See 1 more Smart Citation